The use of the concept of culture in Semiotics - Fiorin, José Luiz (Estudos Semióticos, 2021)
This paper presents the place of culture in semiotic architecture. It starts by examining classic texts that have examined the notion and by considering insufficient the concepts that they operationalize. Drawing on the principle that culture is a semiotics-object, this paper turns to anthropology to find a concept of culture with which it can constitute it. Finally, this paper examines the relations between language and culture, by taking into account that the former is part of the latter but, at the same time, that language renders culture categories and a principle of structurality – the reason why language plays a central role in culture.